# UnfoldN

Posted on 2017-05-03 by nbloomf

This page is part of a series on Arithmetic Made Difficult.

This post is literate Haskell; you can load the source into GHCi and play along.

{-# LANGUAGE NoImplicitPrelude #-}
module UnfoldN
( unfoldN, tacunfoldN, _test_unfoldN, main_unfoldN
) where

import Testing
import Tuples
import DisjointUnions
import NaturalNumbers
import BailoutRecursion
import Lists
import Snoc
import Cat

So far we’ve developed a few functions that operate on lists. But we don’t have a convenient programmatic way to construct lists out of nothing – we’ll remedy this today with a function called $$\unfoldN(\ast)$$. From the name, it sounds like unfold should be the “opposite” (or dual) of a fold. But the full story is a little more complicated than this; the true opposite to fold doesn’t operate on lists at all, but on streams (which we’ll get to later). Roughly speaking, $$\lists{A}$$ is an initial algebra, elements of $$\lists{A}$$ are required to be “finite”, and $$\foldr(\ast)(\ast)$$ condenses a $$\lists{A}$$ element to a single item. Streams, in contrast, are required to be “infinite” and collectively form a terminal algebra and their universal map expands a single item to an infinite structure. All that is to say that the $$\unfoldN(\ast)$$ function we define here is not the real dual of $$\foldr(\ast)(\ast)$$ – which partly explains why it is so complicated looking.

So what will $$\unfoldN(\ast)$$ do? Roughly speaking, we’d like to be able to build up interesting lists of arbitrary size using a small amount of initial data. For example, here is a version of the signature for Haskell’s standard unfoldr function.

unfoldr :: (a -> Maybe (a,b)) -> a -> [b]

This function takes a seed value a and a map that takes an a and returns either Nothing or a pair (a,b), and returns a [b]. We can reasonably infer that this function applies the map to the seed, and if that value is Nothing, returns [], and if the value is an (a,b), make that b the head of our list and repeat with the new seed.

There is a problem with translating this type to $$\lists{A}$$, though. It has to do with the essential finiteness of lists. What happens if the map argument never returns Nothing? Then unfoldr will happily generate an infinite list.

How can we fix this? One strategy would be to impose some kind of constraint on the map so that it must eventually return a Nothing. That may well be possible, but my hunch is that it would make reasoning about unfolds complicated – we’d have to prove that a given map satisfies the constraint before using it.

Another strategy – and the one we will take – is to give unfold a natural number argument that acts as a countdown timer. If it reaches $$\zero$$, we’re done. (This also explains the N in $$\unfoldN(\ast)$$.) This strategy also makes it possible to define $$\unfoldN(\ast)$$ using bailout recursion on $$\nats$$.

Before defining $$\unfoldN(\ast)$$, we need a helper operator, $$\tacunfoldN(\ast)$$, analogous to $$\revcat$$. “tac” is a bad pun on “reverse cat” – since that’s kind of what this operator does.

Let $$A$$ and $$B$$ be sets, and let $$f : A \rightarrow 1 + (A \times B)$$. There is a unique function $\Theta : \lists{B} \times \nats \times A \rightarrow \lists{B}$ such that for all $$a \in A$$, $$x \in \lists{A}$$, and $$n \in \nats$$, we have $\Theta(x,\zero,a) = x$ and $\Theta(x,\next(n),a) = \left\{\begin{array}{ll} x & \mathrm{if}\ f(a) = \lft(\ast) \\ \Theta(\snoc(b,x),n,c) & \mathrm{if}\ f(a) = \rgt((c,b)). \end{array}\right.$ We denote this unique map $$\tacunfoldN(f)$$.

We define $$\varphi : A \times \lists{B} \rightarrow \lists{B}$$ by $\varphi(a,x) = x,$ $$\beta : \nats \rightarrow (A \times \lists{B}) \rightarrow \bool$$ by $\beta = \compose(\const)(\compose(\compose(\isLft)))(\flip(\compose)(\fst)),$ $$\psi : \nats \times (A \times \lists{B}) \rightarrow \lists{B}$$ by $\psi(n,(a,x)) = x,$ and $$\omega : \nats \times (A \times \lists{B}) \rightarrow A \times \lists{B}$$ by $\omega(n,(a,x)) = \left\{\begin{array}{ll} (a,x) & \mathrm{if}\ f(a) = \lft(\ast) \\ (c,\snoc(b,x)) & \mathrm{if}\ f(a) = \rgt((c,b)). \end{array}\right.$ Finally, define $\tacunfoldN(f)(x,n,a) = \bailrec(\varphi)(\beta)(\psi)(\omega)(n,(a,x)).$ For brevity, in this proof we let $$\Omega = \bailrec(\varphi)(\beta)(\psi)(\omega)$$.

First we show that $$\tacunfoldN(f)$$ has the desired properties. To this end, note that $\begin{eqnarray*} & & \tacunfoldN(f)(x,\zero,a) \\ & = & \Omega(\zero,(a,x)) \\ & = & \varphi(a,x) \\ & = & x. \end{eqnarray*}$ Now suppose $$f(a) = \lft(\ast)$$; then $\begin{eqnarray*} & & \tacunfoldN(f)(x,\next(n),a) \\ & = & \Omega(\next(n),(a,x)) \\ & = & \bif{\beta(a,x)}{\psi(a,x)}{\Omega(n,\omega(n,(a,x)))} \\ & = & \bif{\isLft(f(a))}{\psi(a,x)}{\Omega(n,\omega(n,(a,x)))} \\ & = & \bif{\btrue}{\psi(a,x)}{\Omega(n,\omega(n,(a,x)))} \\ & = & \psi(a,x) \\ & = & x \end{eqnarray*}$ as needed. Suppose instead that $$f(a) = \rgt(c,b)$$. Then $\begin{eqnarray*} & & \tacunfoldN(f)(x,\next(n),a) \\ & = & \Omega(\next(n),(a,x)) \\ & = & \bif{\beta(a,x)}{\psi(a,x)}{\Omega(n,\omega(n,(a,x)))} \\ & = & \bif{\isLft(f(a))}{\psi(a,x)}{\Omega(n,\omega(n,(a,x)))} \\ & = & \bif{\bfalse}{\psi(a,x)}{\Omega(n,\omega(n,(a,x)))} \\ & = & \Omega(n,(c,\snoc(b,x))) \\ & = & \tacunfoldN(f)(\snoc(b,x),n,c) \end{eqnarray*}$ as needed.

To see uniqueness, suppose now that $$\Psi : \lists{B} \times \nats \times A \rightarrow \lists{B}$$ has these properties. We show that $$\Psi = \tacunfoldN(f)$$ by induction on $$n$$. For the base case $$n = \zero$$, we have $\begin{eqnarray*} & & \Psi(x,\zero,a) \\ & = & x \\ & = & \tacunfoldN(f)(x,\zero,a) \end{eqnarray*}$ as needed. For the inductive step, suppose we have $$\Psi(x,n,a) = \tacunfoldN(f)(x,n,a)$$ for all $$x$$ and $$a$$ for some $$n$$. Let $$a \in A$$. If $$f(a) = \lft(\ast)$$, then $\begin{eqnarray*} & & \Psi(x,\next(n),a) \\ & = & x \\ & = & \tacunfoldN(f)(x,\next(n),a) \end{eqnarray*}$ as needed. If $$f(a) = \rgt((c,b))$$, then $\begin{eqnarray*} & & \Psi(x,\next(n),a) \\ & = & \Psi(\snoc(b,x),n,c) \\ & = & \tacunfoldN(f)(\snoc(b,x),n,c) \\ & = & \tacunfoldN(f)(x,\next(n),a) \end{eqnarray*}$ as needed.

We can implement $$\tacunfoldN(f)$$ using the definition from the proof, or by pattern matching using the universal property.

tacunfoldN', tacunfoldN
:: (List t, Natural n)
=> (a -> Union () (Pair a b)) -> t b -> n -> a -> t b

tacunfoldN' f x n a = bailoutRec phi beta psi omega n (tup a x)
where
phi (Pair _ w) = w
beta _ (Pair b _) = isLft (f b)
psi _ (Pair _ w) = w
omega _ (Pair b w) = case f b of
Left () -> tup b w
Right (Pair c e) -> tup c (snoc e w)

tacunfoldN f x n a = case unnext n of
Left () -> x
Right k -> case f a of
Left () -> x
Right (Pair c b) -> tacunfoldN f (snoc b x) k c

We should test that these two implementations agree.

_test_tacunfoldN_equiv :: (List t, Equal (t a), Natural n)
=> t a -> n -> Test ((a -> Union () (Pair a a)) -> t a -> n -> a -> Bool)
_test_tacunfoldN_equiv _ _ =
testName "tacunfoldN(x,n,a) == tacunfoldN'(x,n,a)" $\f x n a -> eq (tacunfoldN f x n a) (tacunfoldN' f x n a) And while we’re at it, test that $$\tacunfoldN(f)$$ does satisfy the universal property. _test_tacunfoldN_zero :: (List t, Equal (t a), Natural n) => t a -> n -> Test ((a -> Union () (Pair a a)) -> t a -> a -> Bool) _test_tacunfoldN_zero _ k = testName "tacunfoldN(x,zero,a) == x"$
\f x a -> eq (tacunfoldN f x (zero withTypeOf k) a) x

_test_tacunfoldN_next :: (List t, Equal (t a), Natural n)
=> t a -> n -> Test ((a -> Union () (Pair a a)) -> t a -> n -> a -> Bool)
_test_tacunfoldN_next _ _ =
testName "tacunfoldN(x,next(n),a) == if(isLft(f(a)),x,tacunfoldN(snoc(b,x),n,c))" $\f x n a -> case f a of Left () -> eq (tacunfoldN f x (next n) a) x Right (Pair c b) -> eq (tacunfoldN f x (next n) a) (tacunfoldN f (snoc b x) n c) $$\tacunfoldN(f)$$ interacts with $$\cons$$. We have $\tacunfoldN(f)(\cons(b,x),n,a) = \cons(b,\tacunfoldN(f)(x,n,a)).$ We proceed by induction on $$n$$. For the base case $$n = \zero$$, we have $\begin{eqnarray*} & & \tacunfoldN(f)(\cons(b,x),\zero,a) \\ & = & \cons(b,x) \\ & = & \cons(b,\tacunfoldN(f)(x,\zero,a)) \end{eqnarray*}$ as needed. For the inductive step, suppose the equality holds for all $$a$$, $$b$$, and $$x$$ for some $$n$$. If $$f(a) = \lft(\ast)$$, we have $\begin{eqnarray*} & & \tacunfoldN(f)(\cons(b,x),\next(n),a) \\ & = & \cons(b,x) \\ & = & \cons(b,\tacunfoldN(f)(x,n,a)) \end{eqnarray*}$ as needed, while if $$f(a) = \rgt((c,d))$$ we have $\begin{eqnarray*} & & \tacunfoldN(f)(\cons(b,x),\next(n),a) \\ & = & \tacunfoldN(f)(\snoc(d,\cons(b,x)),n,c) \\ & \href{/posts/arithmetic-made-difficult/Snoc.html#cor-snoc-cons} = & \tacunfoldN(f)(\cons(b,\snoc(d,x)),n,c) \\ & = & \cons(b,\tacunfoldN(f)(\snoc(d,x),n,c)) \\ & = & \cons(b,\tacunfoldN(f)(x,\next(n),a)) \end{eqnarray*}$ as needed. _test_tacunfoldN_cons :: (List t, Equal (t a), Natural n) => t a -> n -> Test ((a -> Union () (Pair a a)) -> t a -> a -> n -> a -> Bool) _test_tacunfoldN_cons _ _ = testName "tacunfoldN(cons(b,x),n,a) == cons(b,tacunfoldN(x,n,a))"$
\f x b n a -> eq (tacunfoldN f (cons b x) n a) (cons b (tacunfoldN f x n a))

$$\tacunfoldN(f)$$ interacts with $$\cat$$.

Let $$A$$ and $$B$$ be sets with $$f : A \rightarrow 1 + (A \times B)$$. For all $$a \in A$$, $$x,y \in \lists{B}$$, and $$n \in \nats$$, we have $\tacunfoldN(f)(\cat(x,y),n,a) = \cat(x,\tacunfoldN(f)(y,n,a)).$

We proceed by induction on $$n$$. For the base case $$n = \zero$$, we have $\begin{eqnarray*} & & \tacunfoldN(f)(\cat(x,y),\zero,a) \\ & = & \cat(x,y) \\ & = & \cat(x,\tacunfoldN(f)(y,\zero,a)) \end{eqnarray*}$ as needed. For the inductive step, suppose the equality holds for all $$x$$, $$y$$, and $$a$$ for some $$n$$. Now let $$a \in A$$; we have two possibilities for $$f(a)$$. If $$f(a) = \lft(\ast)$$, we have $\begin{eqnarray*} & & \tacunfoldN(f)(\cat(x,y),\next(n),a) \\ & = & \cat(x,y) \\ & = & \cat(x,\tacunfoldN(f)(y,\next(n),a)) \end{eqnarray*}$ as needed. Suppose instead that $$f(a) = \rgt((c,d))$$. Now $\begin{eqnarray*} & & \tacunfoldN(f)(\cat(x,y),\next(n),a) \\ & = & \tacunfoldN(f)(\snoc(d,\cat(x,y)),n,c) \\ & \href{/posts/arithmetic-made-difficult/Cat.html#thm-cat-snoc-right} = & \tacunfoldN(f)(\cat(x,\snoc(d,y)),n,c) \\ & = & \cat(x,\tacunfoldN(f)(\snoc(d,y),n,c)) \\ & = & \cat(x,\tacunfoldN(f)(y,\next(n),a)) \end{eqnarray*}$ as needed.

_test_tacunfoldN_cat :: (List t, Equal (t a), Natural n)
=> t a -> n -> Test ((a -> Union () (Pair a a)) -> t a -> t a -> n -> a -> Bool)
_test_tacunfoldN_cat _ _ =
testName "tacunfoldN(cat(x,y),n,a) == cat(x,tacunfoldN(y,n,a))" $\f x y n a -> eq (tacunfoldN f (cat x y) n a) (cat x (tacunfoldN f y n a)) Now we can define $$\unfoldN(\ast)$$ in terms of $$\tacunfoldN(\ast)$$. Let $$A$$ and $$B$$ be sets, with $$f : A \rightarrow 1 + (A \times B)$$. we define $$\unfoldN(f) : \nats \times A \rightarrow \lists{B}$$ by $\unfoldN(f)(n,a) = \tacunfoldN(f)(\nil,n,a).$ In Haskell: unfoldN :: (List t, Natural n) => (a -> Union () (Pair a b)) -> n -> a -> t b unfoldN f = tacunfoldN f nil And $$\unfoldN(\ast)$$ can be characterized as the unique solution of a system of functional equations. Let $$A$$ and $$B$$ be sets with $$f : A \rightarrow 1 + (A \times B)$$. Then $$\unfoldN(f)$$ is the unique map $$g : \nats \times A \rightarrow B$$ such that the following hold for all $$a \in A$$ and $$n \in \nats$$. $\left\{\begin{array}{l} g(\zero,a) = \nil \\ g(\next(n),a) = \left\{\begin{array}{ll} \nil & \mathrm{if}\ f(a) = \lft(\ast) \\ \cons(b,g(n,c)) & \mathrm{if}\ f(a) = \rgt((c,b)). \end{array}\right. \end{array}\right.$ To see that $$\unfoldN(\ast)$$ satisfies the first equation, note that $\begin{eqnarray*} & & \unfoldN(f)(\zero,a) \\ & = & \tacunfoldN(f)(\nil,\zero,a) \\ & = & \nil \end{eqnarray*}$ as needed. We show the second by induction on $$n$$. For the base case $$n = \zero$$, if $$a \in A$$ and $$f(a) = \lft(\ast)$$ we have $\begin{eqnarray*} & & \unfoldN(f)(\next(\zero),a) \\ & = & \tacunfoldN(f)(\nil,\next(\zero),a) \\ & = & \nil \end{eqnarray*}$ as needed, and if $$f(a) = \rgt((c,b))$$ we have $\begin{eqnarray*} & & \unfoldN(f)(\next(\zero),a) \\ & = & \tacunfoldN(f)(\nil,\next(\zero),a) \\ & = & \tacunfoldN(f)(\snoc(b,\nil),\zero,c) \\ & = & \snoc(b,\nil) \\ & \href{/posts/arithmetic-made-difficult/Snoc.html#cor-snoc-nil} = & \cons(b,\nil) \\ & = & \cons(b,\tacunfoldN(f)(\nil,\zero,a)) \\ & = & \cons(b,\unfoldN(f)(\zero,a)) \end{eqnarray*}$ as needed. For the inductive step, suppose the equality holds for all $$a$$ for some $$n$$. Let $$a \in A$$. If $$f(a) = \lft(\ast)$$, we have $\begin{eqnarray*} & & \unfoldN(f)(\next(n),a) \\ & = & \tacunfoldN(\nil,\next(n),a) \\ & = & \nil \end{eqnarray*}$ as needed, while if $$f(a) = \rgt((c,b))$$ we have $\begin{eqnarray*} & & \unfoldN(f)(\next(n),a) \\ & = & \tacunfoldN(f)(\nil,\next(n),a) \\ & = & \tacunfoldN(f)(\snoc(b,\nil),n,c) \\ & \href{/posts/arithmetic-made-difficult/Snoc.html#cor-snoc-nil} = & \tacunfoldN(f)(\cons(b,\nil),n,c) \\ & = & \cons(b,\tacunfoldN(f)(\nil,n,c)) \\ & = & \cons(b,\unfoldN(f)(n,c)) \end{eqnarray*}$ as needed. To see that $$\unfoldN(f)$$ is unique we again induct on $$n$$. Suppose $$\Psi$$ is another solution. For the base case $$n = \zero$$ note that $\begin{eqnarray*} & & \Psi(\zero,a) \\ & = & \nil \\ & = & \unfoldN(f)(\zero,a) \end{eqnarray*}$ as needed. For the inductive step, suppose we have $$\Psi(n,a) = \unfoldN(f)(n,a)$$ for all $$a$$ for some $$n$$, and let $$a \in A$$. If $$f(a) = \lft(\ast)$$, then $\begin{eqnarray*} & & \Psi(\next(n),a) \\ & = & \nil \\ & = & \unfoldN(f)(\next(n),a) \end{eqnarray*}$ as needed, while if $$f(a) = \rgt((c,b))$$ we have $\begin{eqnarray*} & & \Psi(\next(n),a) \\ & = & \cons(b,\Psi(n,c)) \\ & = & \cons(b,\unfoldN(f)(n,c)) \\ & = & \unfoldN(f)(\next(n),a) \end{eqnarray*}$ as needed. _test_unfoldN_zero :: (List t, Equal (t a), Natural n) => t a -> n -> Test ((a -> Union () (Pair a a)) -> a -> Bool) _test_unfoldN_zero t k = testName "unfoldN(zero,a) == nil"$
\f a -> eq (unfoldN f (zero withTypeOf k) a) (nil withTypeOf t)

_test_unfoldN_next :: (List t, Equal (t a), Natural n)
=> t a -> n -> Test ((a -> Union () (Pair a a)) -> n -> a -> Bool)
_test_unfoldN_next t _ =
testName "unfoldN(next(n),a) == if(isLft(f(a)),nil,cons(b,unfoldN(n,c)))" \$
\f n a -> case f a of
Left ()          -> eq (unfoldN f (next n) a) (nil withTypeOf t)
Right (Pair c b) -> eq (unfoldN f (next n) a) ((cons b (unfoldN f n c)) withTypeOf t)

## Testing

Suite:

_test_unfoldN ::
( TypeName a, Equal a, Show a, Arbitrary a, CoArbitrary a
, TypeName (t a), List t, Equal (t a), Arbitrary (t a), Show (t a)
, TypeName n, Equal n, Show n, Arbitrary n, Natural n
) => Int -> Int -> t a -> n -> IO ()
_test_unfoldN size cases t n = do
testLabel1 "unfoldN" t

let args = testArgs size cases

runTest args (_test_tacunfoldN_equiv t n)
runTest args (_test_tacunfoldN_zero t n)
runTest args (_test_tacunfoldN_next t n)
runTest args (_test_tacunfoldN_cat t n)
runTest args (_test_tacunfoldN_cons t n)

runTest args (_test_unfoldN_zero t n)
runTest args (_test_unfoldN_next t n)

Main:

main_unfoldN :: IO ()
main_unfoldN = do
_test_unfoldN 20 100 (nil :: ConsList Bool)  (zero :: Unary)
_test_unfoldN 20 100 (nil :: ConsList Unary) (zero :: Unary)